Da regra aos fatos: Condicionantes da aquisiç\~ao de produtos da agricultura familiar para a alimentaç\~ao escolar em municípios brasileiros - Alexandre Arbex Valadares; Fabio Alves; Lillian Bastian; Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– Public policies of national scope in the context of Brazilian federalism contain a diversity of challenges for their implementation, given the complexity of the contexts in which they face and the territorial magnitude of their scope. The theme of school feeding, structured around the National School Feeding Program (PNAE), present in all municipalities, is largely faced with these challenges. This study proposed to raise different administrative, political and institutional responses adopted, within the scope of the local application of federal resources transferred by the PNAE, to promote the purchase of food from family farming, pursuant to article 14 of Law No. 11,947/2009. For this purpose, four municipalities were chosen - Bonfinópolis de Minas and Brasilândia de Minas, in the state of Minas Gerais, and Ourém and Santa Izabel do Pará, in Pará - which, despite having similar geographic characteristics, record different performances in complying with this new rule. The cases analyzed express a set of methods aimed at understanding the dynamics surrounding the State in action, demonstrating concrete aspects of the challenges and potentials associated with the insertion of this public in institutional markets, while emphasizing possible factors for the potentialization of this instrument in Brazilian territory.
Keywords: H83; J23; 330; school feeding; family farming; public administration; federalism; local development